Marked heterogeneity in the diagnosis of compensated cirrhosis of patients with chronic hepatitis C virus infection in a real‐world setting: A large, multicenter study from Japan. Issue 8 (31st January 2020) - Toyoda, Hidenori; Atsukawa, Masanori; Watanabe, Tsunamasa; Nakamuta, Makoto; Uojima, Haruki; Nozaki, Akito; Takaguchi, Koichi; Fujioka, Shinichi; Iio, Etsuko; Shima, Toshihide; Akahane, Takehiro; Fukunishi, Shinya; et al.
Abstract: Background and Aim: The presence of cirrhosis is an important factor for the management of patients with hepatitis C virus (HCV) infection and it determines the duration of treatment for HCV with the direct‐acting antiviral (DAA) regimen of glecaprevir (GLE) and pibrentasvir (PIB), that is, 8 or 12 weeks, if patients do not have a history of DAA failure. However, in real‐world settings, determination of cirrhosis depends on the discretion of the attending hepatologists, and it is unclear whether compensated cirrhosis was homogenously diagnosed or not. In this study, we investigated the real‐world diagnosis of cirrhosis by characterizing DAA‐naïve patients who underwent a 12‐week GLE/PIB regimen in whom cirrhosis was diagnosed, comparing their characteristics with those of patients who underwent an 8‐week regimen in whom cirrhosis was absent. Methods: In a large, multicenter cohort study, we compared background characteristics and treatment outcomes among DAA‐naïve patients who underwent an 8‐week versus a 12‐week GLE/PIB regimen. Results: Among 977 patients enrolled, 296 (30.3%) were determined to have cirrhosis and underwent a 12‐week regimen. Some patient characteristics largely overlapped between the two groups, including liver fibrosis indices. Sustained viral response rates were similar between groups after adjusting liver fibrosis index with propensity score matching. Conclusion: Although adequately diagnosed, the determination of cirrhosis varied widely among institutions or by hepatologists in real‐world settings, and the severity of liver fibrosis overlapped significantly between patients in whom compensated cirrhosis was determined to be present and patients in whom cirrhosis was absent. Virologic efficacy was similar after adjusting for the degree of liver fibrosis.